Stuktur Interogatif Penyidik Pada Saksi Ahli Pidana Kasus Delik Aduan Di Polda Jateng - Ika Arifianti (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
Legal language can develop according to the suspect's confession in the BAP process. BAP (The investigation report) is a state secret that may not be published to the general public. However, in the interests of this research, the investigation report process is allowed only to the extent needed. The novelty of this research is in the realm of research data collection, namely interrogative investigators with criminal law experts. The results of the interrogative are studied, so that the results of this research become a new contribution to the world of linguistic and police research. After all, qualified investigators are needed. . Normative legal research consists of research into the principles of law. This normative legal approach is related to legal research which is called legal research.  The data in this study are sourced from the BAP of complaints in 2013 in cases of domestic violence committed by members of the National Police. The results of this study explain the discourse structure of the investigation report of criminal experts in the complaint offense case at the Central Java Regional Police with the following findings. (1) opening structure, content structure, and closing, which clarifies the content structure related to the identity of expert witnesses according to their expertise, statements of truth reporting related to the legal domain, clarity based on information and evidence. . This research can be a reference for further research in the field of pragmatics, and critical pragmatics and can be followed up in the field of forensic linguistics. The study of pragmatics and forensic linguistics is an applied linguistic field that deserves to be researched in the context of linguistic scientific development efforts. This research data can be developed for forensic linguistics research. Forensic linguistics is a new field of science in the field of applied linguistics